The Role of the State in Sharia Economic Regulation from a Political Economic Perspective - Mohammat Abdul Gofar; Fathur Rozi; Mashudi (Penerbit Hellow Pustaka, 2025)
Sharia economy is a system that integrates Islamic values ​​in economic activities, based on the principles of justice, balance, and sustainability. In the context of political economy, the role of the state is crucial to regulate and support the implementation of sharia economy through regulations that are in accordance with sharia principles. This study aims to analyze how the state can play a strategic role in sharia economic regulation, by examining various policies, regulations, and challenges faced. A descriptive-analytical approach is used in this study to understand the role of the state as a regulator, facilitator, and supervisor in realizing competitive sharia economic governance. The results of the study show that regulations issued by the state have a significant influence on the development of sharia economy, especially in the banking, finance, and trade sectors. However, challenges such as regulatory gaps, lack of public understanding, and weak cross-sector coordination are still obstacles that need to be overcome. Therefore, synergy is needed between the state, scholars, and economic actors to create an economic environment that is in line with sharia principles.